FEATURES OF MUTUAL INESTMENT FUNDS INVESTMENT IN RUSSIA IN THE CURRENT CONDITIONS - Olga V. Pomaskina (Статистика и экономика)
The article describes the types and categories of mutual funds in Russia, analyzes development trends in 2013. A comparative analysis of mutual funds and general funds of bank management highlights global trends of collective investment funds.